A Novel Prime Number Path Tracing Scheme Using Clos Network (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
A novel scheme of path tracing in all-optical network (AON) is described, every node has a prime number and as data packet travels in the network prime number tag is multiplied with the other node tag. At receiver end factorization is done to measure the travelled path. This technique is implemented with the help of encoder which helps to multiply the prime number tags. This scheme has highest QoS than the scheme which use optical cross connects (OXC).In this scheme OXC is replaced with the clos network which gives better performance than system with OXC.